PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN ORIENTASI KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA: (Studi Survei pada Siswa Kelas XII SMA Negeri 27 Garut) - Wida Mardiah; Tjutju Yuniarsih; Lili Adi Wibowo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine how the influence of entrepreneurial education and entrepreneurial orientation on entrepreneurial intention. This research method uses a correlation study with a quantitative approach. The subjects of this study were students of SMAN 27 Garut. The population in this study amounted to 124 students with a sample of 95 students. Analysis of the data in this study using SPSS 25. The results of this study indicate that students of SMAN 27 Garut have a high level of entrepreneurial education, have a high level of entrepreneurial orientation, and have a high level of entrepreneurial intention. The results of the data analysis of this study also show that entrepreneurship education has a significant effect on entrepreneurial intention and entrepreneurial orientation has a significant effect on students' entrepreneurial intentions